ISOLASI DAN UJI AKTIVITAS BAKTERI PELARUT FOSFAT DARI RHIZOSFER TANAMAN PADI (Oryza sativa L.) PADA FASE VEGETATIF DAN GENERATIF - Saida, Saida; Samsul, N.; Edy, Edy (AGROTEK: Jurnal Ilmiah Ilmu Pertanian, 2024)
Phosphorus (P) is a very important macronutrient for plant growth and development. Plants cannot fully absorb phosphate in the soil, only 25% can be absorbed by plants while Al binds 75% in the soil. Plants absorb P from the soil in the form of phosphate ions, especially in the form of H2PO4- and HPO42- which are present in soil solutions. H2PO4 ion is more common in acidic soils, while higher pH (> 7) forms HPO42- is more dominant. The lack of P dissolved in the soil causes the plant to get P intake from other sources such as fertilizers. Efforts to increase the efficiency of Phosphate dissolution, currently the use of Phosphate solubilizing microbes have begun to be developed. This study aims to determine the number of isolated bacterial colonies, the ability of phosphate-solubilizing bacteria, and the levels of P-available before and after giving phosphate-solubilizing bacterial isolates. This research was conducted at the Laboratory of Plant Pests and Diseases and in the Laboratory of Soil and Environmental Conservation, Faculty of Agriculture, Universitas Muslim Indonesian, Makassar, Indonesia, from November to December 2020. The materials used in this study were HVS paper, aluminum foil, plastic wrap, labels, rubber, Pikovskaya media, sterile distilled water, plastic, cotton, tissue, 70% alcohol, rubbing alcohol, NA (Natrium Agar) media, soil samples from the vegetative and generative phases of rice rhizosphere from Tebba Village, Salomekko District, Bone Regency. This research method is a qualitative exploratory research based on data analysis. The results of this study indicated that the vegetative phase 3 rice isolates with 10-5 dilution had the highest number of colonies, namely 9,200,000 CFU /ml. Plant generative phase 3 rice isolate at 10-5 dilution had the highest average phosphate solubility with an IPF value of 5.56. Plant generative phase 3 rice isolate had the highest average P-available before and after the addition of Phosphate Solubilizing Bacteria isolates, namely 3.83 ppm, and after the addition of Phosphate Solubilizing Bacteria isolates increased to 9.58 ppm.